Perilaku Penggunaan Tik Tok Sebagai Media Promosi Pebisnis - Linda Saffira; Ginanjar Rahmawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This research aims to see the effect of easy to use, low cost promotion, target advertising on the decision to use Tiktok as a business promotion medium. The number of respondents used is 97 respondents, the sample technique is non-probability sampling and the method uses quantitative because business owners who use tiktok for promotion are infinite. The primary data is obtained by using a questionnaire method distributed to business owners, the data is then processed through the SPSS application. In this study, it was found that the easy to use and low cost promotion variables did not affect the decision to use promotions using Tiktok social media, while the targeted advertising variables had an influence on decisions to use Tiktok social media promotions.